Погребение позднего бронзового века в кургане № 1 у с. Брынзений Ной (о культурно-историческом блоке Ноуа-Сабатиновка) - Агульников, С.М. (Материалы по археологии Северного Причерноморья, 2019)
В 2013 году экспедиция в составе сотрудников Национального Агентства Археологии Молдовы и Института Культурного Наследия АН РМ проводила охранные археологические исследования в зоне реконструкции автомобильной магистрали Саратень – Сорока у с. Брынзений–Ной Теленештского р-на р. Молдова (Agulnicov, Mistreanu, Popovici 2014: 203–216). In this article is published a funeral complex of the Late bronze period one tomb number 1 near the village Brinzenii- noi in Moldavia, he is located in border zone of the the silvosteppe and steep. The funeral rite of passage and inventory is corresponding to culture historical block of ne Sabatinovka, and in the first grave has correspondence in Noua culture, and also the Sabatinovka culture a few features of funeral rite of passage is borrowed from Srubnayia culture of the North-pontic territory. The funeral complex is dated XVI–XIII century’s b.Cr.